DESAIN APLIKASI LAPORAN KEUANGAN USAHA KOS-KOSAN BERDASARKAN SAK EMKM MENGGUNAKAN MICROSOFT ACCESS - Merry Ligia Sael; Ririn Fadilah Baso; Joseph Tangon (Jurnal Bisnis Terapan, 2021)
Abstract The purpose of this study was to design existing financial reports using applications that are easier, faster, more complete, accurate, and timely in presenting financial statement information. This research was conducted at the Kost Katto 2 Kec. Mapanget, Manado. The data obtained from the author's interviews with business owners and employees. The research method used was a qualitative method with a descriptive approach. Data collection was carried out by means of observation, interviews, and literature study.The results showed that in preparing financial reports based on SAK EMKM using Microsoft Access, all difficulties and problems faced in preparing financial reports could be resolved. This arrangement was based on the accounting cycle by preparing the required forecast tables, after which it can input transactions and can see the results of the financial statement design in the form of an income statement, a statement of financial position, and notes to financial statements. The recommendation from the results of this study is that Kost Katto 2 should make bookkeeping reports in accordance with existing standards and make financial reports using the Microsoft Access application program designed based on SAK EMKM Keywords: Application design, financial report, SAK EMKM